In-vitro evaluation of commonly used beverages on tensile strength of different suture materials used in dental surgeries. Issue 48 (25th November 2020) - Abullais, Shahabe Saquib; Alqahtani, Nabeeh Abdullah; Alkhulban, Raed Mofarh; Alamer, Sarah Hassan; Khan, Abdul Ahad; Pimple, Sandeep
Abstract : Abstract: Sutures are used for the approximation of incised flaps, assistance in primary healing, and hemorrhage control. In oral and periodontal surgery, the appropriate selection of suture material is vital for favorable healing. The aim of the present in-vitro experiment was to evaluate the tensile strengths of 4 different types of suture materials (silk, polygalactine 910, polypropylene, chromic catgut) by simulating potential short-term intraoral exposure to various beverages (saliva, Arabic coffee, tea, cola). A total of 280 suture specimens were prepared, out of which 10 specimens from each group were selected for pre-immersion testing. Remaining suture specimens were immersed in 4 different thermostatically controlled media (1 control [artificial saliva], 3 tests [Cola drink, Arabic coffee, Tea]). Tensile strength was measured at pre-immersion, 3, 7, and 14 days using a universal tensile testing machine. The maximum load required to break the suture material was recorded in Newton. At day 3, tea caused significant reduction in tensile strength of silk and cola caused significant reduction in tensile strengths of polygalactine 910 and chromic catgut. Whereas, at day 7, silk and polypropylene retained their tensile strengths better than others. The authors recommend precaution in the use of these beverages in the first postoperative week, to avoid adverse effect on the mechanical strength of sutures. When exposure to these beverages are anticipated, it is better to use polypropylene sutures that resists rapid fall in tensile strengths in the early postoperative period.